Ablative therapies versus partial nephrectomy for small renal masses – A systematic review and meta-analysis. (January 2022) - Chan, Vinson Wai-Shun; Abul, Ahmad; Osman, Filzah Hanis; Ng, Helen Hoi-Lam; Wang, Kaiwen; Yuan, Yuhong; Cartledge, Jon; Wah, Tze Min
Abstract: Background: High quality studies and reviews on the management of small renal masses (SRM) are lacking. This review aims to compare oncological outcomes in patients undergoing ablative therapies (AT) or partial nephrectomy (PN) for T1a or T1b SRM. Material and methods: Medline, EMBASE, Cochrane CENTRAL and conference proceedings were searched on the 15th July 2020 for comparative studies respective to our research question. The ROBINS-I tool and the GRADE approach were used to assess any risk of biases and certainty of evidence in the included studies. The review is registered on PROSPERO. Results: 1, 748 records were retrieved. 32 observational studies and 1 RCT integrating 74, 946 patients were included. Patients undergoing AT patients are significantly older than PN patients (MD 5.70, 95%CI 3.83–7.58). In T1a patients, AT patients have significantly worse overall survival (HR 1.64, 95%CI 1.39–1.95). Local recurrence-free survival is similar with PN in patients with longer than five-years follow up (HR 1.54, 95%CI 0.88–2.71). AT patients also have similar cancer-specific survival (CSS), metastasis-free survival, disease-free survival, significantly fewer post-operative complications (RR 0.72, 95%CI 0.55–0.94), and a smaller decline in estimated glomerular filtration rate post-operatively (MD: -7.42, 95%CI -13.1 to −1.70) compared to those undergoing PN. Evidence contradicts in T1b patients for oncological outcomes. Conclusions: AT have similar long-term oncological durability; lower rates of complications and superior kidney function preservation compared to PN. Given the low quality of evidence, AT is a reasonable alternative to PN in frail and co-morbid patients. Long-term high-quality studies are needed to confirm the potential benefits of AT, especially in T1b patients. PROSPERO Registration: CRD42020199099. Highlights: Ablative therapies and partial nephrectomy result in comparable long-term oncological outcomes. Ablative therapies have significantly less post-operative complications compared to partial nephrectomy. Renal function preservation is significantly lower in patients undergoing Fig. 1 ablative therapies compared to partial nephrectomy. Standardized reporting and randomised evidences are needed to obtain high-quality evidence.